Riding Solo to the Top of the World - Jani, Gaurav (Dirt Track Productions, 2006)
Verzio FF submission Riding Solo is a film about filmmaker Gaurav Jani's solo motorcycle journey from Mumbai to one of the remotest places in the world, the Changthang Plateau in Ladakh, bordering China. The film is even more extraordinary for the fact that Jani was a one-man crew who loaded his 200 kg bike with over 100 kgs of equipment/supplies and set off on a journey to one of the world's most difficult terrains.